2018
DOI: 10.5387/fms.2018-09
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy for esophageal squamous cell carcinoma: a review

Abstract: Cancer vaccines and immune checkpoint inhibitors (ICI) have recently been employed as immunotherapies for esophageal squamous cell carcinoma (ESCC). Cancer vaccines for ESCC have yielded several promising results from investigator-initiated phase I and II clinical trials. Furthermore, a Randomized Controlled Trial as an adjuvant setting after curative surgery is in progress in Japan. On the other hand, ICI, anti-CTLA-4 mAb and anti-PD-1 mAb, have demonstrated tumor shrinkage and improved overall survival in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…The high expression of CD38 has been reported to be a favorable prognosis factor in ESCC [15], prostate cancer [12], hepatic caner [17] and triple negative breast cancer (TNBC) [23]. CD38 participates in the germinal center reaction with inducible co stimulator Ligand competitively and stimulated the anti-tumor immunity [24,25]. Chen et al found no association between CD38 expression and OS in patients with early stage of lung cancer [21].…”
Section: Discussionmentioning
confidence: 99%
“…The high expression of CD38 has been reported to be a favorable prognosis factor in ESCC [15], prostate cancer [12], hepatic caner [17] and triple negative breast cancer (TNBC) [23]. CD38 participates in the germinal center reaction with inducible co stimulator Ligand competitively and stimulated the anti-tumor immunity [24,25]. Chen et al found no association between CD38 expression and OS in patients with early stage of lung cancer [21].…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, the incidence and mortality rates of EC were reported to be extremely high, accounting for 25% of the total cancer-related mortality (3). Surgery, medication and radiation therapy are the main treatment options for ESCC; however, survival rates remain poor, rendering further effort for developing new therapeutic strategies necessary (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…The NLRP3 inf lammasome, which could initiate inflammatory responses, is considered to contribute to the SHUANG YU 1 , JIAN-JIAN YIN 1 , JIN-XIN MIAO 2 , SHI-GANG LI 1 , CHEN-ZHENG HUANG 1 , NING HUANG 3 , TIAN-LI FAN 1 , XIANG-NAN LI 4 , YAO-HE WANG 5 , SHENG-NA HAN 1 and LI-RONG ZHANG 1,6 development of cancer-related inflammation and play a crucial role in tumorigenesis (10,11). Recent evidence has also shown that the malignant phenotype of human melanoma, as well as lung and colon carcinoma, are associated with the excessive expression and constitutive activation of the NLRP3 inflammasome (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…1 Squamous cell carcinoma and adenocarcinoma are the two predominant histologic subtypes of esophageal cancer, with the former accounting for >90% of all cases of esophageal cancer. 1,2 Although the 5-year global survival rate of esophageal squamous cell carcinoma (ESCC) patients (30-40%) has improved due to the advancements in diagnostic and treatment modalities, the cancer is still detected in advanced stages in many patients and the efficacy of current systematic treatments, especially chemotherapy, remains unsatisfactory. 2,3 Therefore, developing novel therapeutic strategies and agents remains an urgent need for ESCC therapy.…”
Section: Introductionmentioning
confidence: 99%